Influência de um protocolo de treinamento em circuito na gordura intermuscular da coxa, composição corporal, parâmetros clínicos, funcionais e metabólicos de pacientes com osteoartrite de joelho - Almeida, Aline Castilho de (Universidade Federal de São Carlos, 2018)
Objective: To investigate the influence of a circuit training protocol on body composition, thigh intermuscular fat, self-reported physical symptoms and physical function, physical performance, metabolic parameters, muscle strength and quality in patients with knee osteoarthritis (OA). Three studies were carried out: I: Influence of a progressive circuit training protocol on intermuscular adipose tissue of patients with knee osteoarthritis: protocol for a randomized controlled clinical trial; II: Influence of a periodized circuit training protocol on the body composition of patients with knee osteoarthritis: results from a randomized controlled clinical trial; III: A periodized circuit training protocol reduces intermuscular adipose tissue of the patients knee with osteoarthritis: results from a randomized controlled clinical trial. Methods: 61 subjects with knee OA grades II and III, aged 40-65 years, and BMI <30kg / m², were randomized into three groups: periodized CT (n= 20); conventional strength training (ST) (n= 21) and educational protocol (EP) (n= 20). CT and ST participated in protocols of 14 weeks, 3 times per week. CT performed mild, moderate and intense exercises, progressively distributed in a circuit model. ST performed resisted exercises and the EP participated in lectures about healthy living. Baseline and post-intervention assessments were performed for all participants. Study II investigated body composition, functional performance tests (30-second chair test, 40-meter walk test, stair climb test), and questionnaires about pain, self-reported physical function and stiffness, and thoughts and feelings about pain. Study III investigated thigh composition, muscle strength of knee extensors and flexors, and muscle quality. Results: The results of Study II show that only the participants in the CT group showed a reduction of visceral adipose tissue, improvements in overall body composition, blood concentration of HDL and systolic and diastolic blood pressure after 14 weeks of training compared to the other groups. Both training strategies showed similar benefits in improving pain, stiffness, physical function and pain catastrophism, functional performance, and muscle strength in patients with knee OA. The results of Study III show that only the CT showed a reduction in the intermuscular fat of the thigh after 14 weeks of training. Both training groups showed muscle mass gain, muscle strength and muscle quality after 14 weeks of training; however, the CT presented muscle strength gain only for the knee extensors, while the ST presented a gain for the knee extensors and flexors. Conclusion: CT improves the body composition of patients with knee OA, reducing visceral fat, and intermuscular fat of the thigh. This training strategy reduces systolic and diastolic blood pressure, and increases HDL concentration. CT was as effective as ST in muscle mass gain in the thigh, muscle strength gain of knee extensors, improvement in muscle quality, self-reported pain, physical function and stiffness, and functional performance in this sample.
Influence of a circuit training protocol on thigh intermuscular fat, body composition, clinical, functional and metabolic parameters of patients with knee osteoarthritis
Keywords: Fisioterapia; Osteoartrite de joelho; Composição corporal; Tomografia Computadorizada Por Raios X; Dor; Força Muscular; Função Física; Physical therapy; Knee osteoarthritis; Body composition; X-ray computed tomography; Pain; Muscle strength; Physical function; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL